Enamel and Dentin Caries Risk Factors of Adolescents in the Context of the International Caries Detection and Assessment System (ICDAS): A Longitudinal Study - Wang, Ketian; Pang, Liangyue; Fan, Cancan; Cui, Tianqiang; Yu, Lixia; Lin, Huancai (Frontiers in Pediatrics, 2020)
Objective The objective of this study was to identify risk factors for enamel and dentin caries in adolescents. Method This one-year longitudinal study was conducted in 2018 and 2019; 13- to 14-year-old adolescents were recruited. The merged International Caries Detection and Assessment System (ICDAS) was used to identify caries. The relationships between the caries increment and variables were analysed with a zero-inflated negative binomial (ZINB) regression model. Results A total of 1016 participants completed the assessment. The ZINB analysis found that individuals with caries at baseline were more likely to develop new dentin caries. Females, or individuals who had a high cariostat score had an increased likelihood of having a high ∆D4-6MFT score. Among the caries-free adolescents at baseline, females, or individuals who consumed snacks once or more than once a day were more likely to develop caries. Individuals from one-child families, who used fluoride toothpaste, and who had a high saliva buffering capability (pH≥4.25) had an increased likelihood of a low △D1-6MFT score. Conclusion The results suggest that there are some specific risk factors of initiating of enamel caries in adolescents, including the frequency of snack consumption, sex, saliva buffering capability, fluoride toothpaste usage and belonging to a one-child family. In all adolescents, most of whom have enamel caries, the dentin caries risk factors were past caries experience, cariostat score and sex.